My friend and I have an argument.
Imagine a person riding on a bike, then stretching one of his hands completely aside while holding a ball, releasing its grip completely.
basic logic tells me that if that person is fast enough the ball should stick to his hand instead of falling off, why is it? what are the forces applied to the ball in this situation?
Easy Math Editor
This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.
When posting on Brilliant:
*italics*
or_italics_
**bold**
or__bold__
paragraph 1
paragraph 2
[example link](https://brilliant.org)
> This is a quote
\(
...\)
or\[
...\]
to ensure proper formatting.2 \times 3
2^{34}
a_{i-1}
\frac{2}{3}
\sqrt{2}
\sum_{i=1}^3
\sin \theta
\boxed{123}
Comments
I assume that the plane of the person's hand is perpendicular to the direction of motion. Suppose he is going very fast. The forces look like the diagram below. The hand normal force balances the air resistance, and if the speed is just right, the friction force from the hand can balance the gravity force on the ball.
But now I'm not sure how the torques balance. The real-world situation is considerably more complicated than the picture below. It would be cool to try this in a wind tunnel.
∑Fy=FN−Fg
where Fg = mg = (mbike+mperson+mball) g
∑Fx=Fp−(Ff+Fd)
Where:
Fp is the force the biker is applying to the pedals to move the bike forward
Ff is the force of friction the road applies to the tires
Fd is the air resistance; it might be negligible for this problem, but in the real world this would apply.
Example: Let the following conditions be true...
v0 = 10sm
mbike = 15kg
mperson = 60kg
mball = 0.80kg
g = 10s2m
μfriction = 0.01
Fdrag≈0
Fpedaling = 10N
TO FIND: ∑Fx
∑Fx = Fp−(Ff+Fd)) = 10 N−(μFN+0)
μFN = (0.01)Fg = (0.01)(15kg+60kg+0.80kg) 10s2m = 7.58 N
∑Fx = Fp−(Ff+Fd) = 10 N−(7.58 N) = 2.42 N
∑Fx = 2.42 N